What supports the deep chlorophyll maximum in acidic lakes? The role of the bacterial CO2 production in the hypolimnion. (30th December 2019) - Soria‐Píriz, Sara; Lara, Miguel; Jiménez‐Arias, Juan Luis; Papaspyrou, Sokratis; Úbeda, Bárbara; García‐Robledo, Emilio; Bohórquez, Julio; Gálvez, José Ángel; Revsbech, Niels Peter; Corzo, Alfonso
Abstract: The interactions between phytoplankton, bacteria and resources, irradiance, and nutrients, leading to the formation of deep chlorophyll maxima (DCMs), are little understood in acid lakes. In "El Sancho" reservoir (Iberian Pyritic belt, Huelva, Spain), an acid mine drainage impacted waterbody (pH 3.5–4.0), a strong DCM forms in the metalimnion during the stratification period. The DCM was located always below the 1% irradiance level, where the decreasing irradiance profile overlapped with a dissolved inorganic carbon concentration (CO2 ) gradient decreasing upward from the hypolimnion. The DCM was dominated by the chlorophyte Carteria sp. and showed the highest volumetric photosynthetic and dark respiration rates. The DCM, however, only contributed around 20% of water column integrated gross primary production, while it accounted for 54–66% of water column chlorophyll. The total bacterial abundance correlated significantly with the CO2 concentration ( r = 0.74). To test the hypothesis of a possible dependence of the formation of the DCM in acid lakes on the production of CO2 by heterotrophic bacteria, a one‐dimensional reactive transport model (DCM‐CO2 ) was developed and tested. The DCM‐CO2 model simulated the vertical distribution of chlorophyll ( R 2  > 0.63) and the vertical profile of CO2 rather accurately ( R 2  > 0.79), the position of DCM depending on both light penetration and an upward flux of CO2 produced by hypolimnetic heterotrophic bacteria. Overall, the results support the hypothesis of microbial degradation of organic matter being a source of CO2 for acid lake primary producers at the DCM.